Development of an Energy Teaching Kit to Foster Computational Thinking Skills of Primary Students in the Renewable Energy Subject - Swasti Maharani; Irna Tri Yuniahastuti; Vera Dewi Susanti; Fida Rahmantika Hadi; Putri Sindy Wibisono (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research aimed to develop the Energy Teaching Kit as a learning medium to enhance elementary students’ computational thinking skills in science learning. The study employed a Research and Development (R&D) design, utilizing the ADDIE model, which comprises the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants were elementary school students from both public and private schools in Madiun City. Data were collected through tests and questionnaires during the implementation phase. The results indicate that the developed medium achieved a validity score of 86%, demonstrating that its content, structure, and functionality meet expert criteria. The practicality level reached 87.05%, indicating that the medium is easy to use and has been positively received by teachers and students. Its effectiveness is supported by an N-gain score of 52.76%, indicating a moderate level of improvement in students’ computational thinking skills. Overall, these findings confirm that the Energy Teaching Kit is valid, practical, and effective for classroom use. Future research may examine its integration with digital sensors, its scalability across different grade levels, and the support it provides for teacher professional development to optimize implementation.